Constructing tests of cognitive abilities for schooled and unschooled children - Alcock, K; Holding, P; Mung'ala-Odera, V; Newton, C (2008)
It is frequently necessary to assess children with little or no schooling to determine their level of cognitive functioning, especially in developing countries. It is not possible, however, to assume that assessments will hold equal validity for children with and without the experience of schooling. The authors, therefore, set out to create a battery of tests suitable for both schooled and unschooled children. They assessed 973 schooled and 645 unschooled children in rural coastal Kenya using culturally adapted cognitive tests. Significant effects of age and schooling were found on all tests. On some tests (verbal knowledge, speeded figure matching, and pattern copying), unschooled children did not improve as much with age as schooled children. The effects of length of exposure to schooling and of age were greater than that of initial enrollment in school. The authors conclude that it is possible to assess unschooled children, but test batteries must be carefully constructed and standardized. © 2008 Sage Publications.